Virtual screening of low molecular weight mushrooms compounds as potential Mdm2 inhibitors. - Froufe, Hugo J.C. (2013)
In some human cancer cases, the activity of p53 is inhibited by overexpressed Mdm2. Mdm2 acts as an ubiquitin ligase, resulting in p53 ubiquitination and subsequent p53 proteasomal degradation. The disruption of the Mdm2-p53 interaction using small-molecule inhibitors is recognized as a promising strategy for anticancer drug design. Mushrooms are an important source of powerful compounds with antitumor properties. In this study, we present the first virtual screening of low molecular weight compounds present in mushroom as potential Mdm2 inhibitors. A re-docking and cross-docking method was used to validate the virtual screening protocol. The steroids: ganoderic acids X (Ki=16nM), Y (Ki=22nM) and F (Ki=69nM); 5,6-epoxy-24(R)-methylcholesta-7,22-dien-3β-ol (Ki=74nM) and polyporenic acid C (Ki=59nM) stand out as the top ranked potential inhibitors of Mdm2. The docking pose of the most promising compounds were carefully analysed and the information provided shows several interesting starting points for further development of Mdm2 inhibitors.